2010
DOI: 10.1111/j.1365-3024.2009.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lymphocyte populations in suckling piglets during primary infections withIsospora suis

Abstract: Isospora suis, a common intestinal parasite of piglets, causes neonatal porcine coccidiosis, which results in reduced and uneven weaning weights and economic losses in pig production. Nevertheless, there are no detailed studies available on the immune response to I. suis. The aim of this study was to carry out phenotypical characterization of lymphocytes during primary infections on day 3 after birth. Infected and noninfected piglets were investigated between days 7 and 16 after birth. Lymphocytes from the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 41 publications
(71 reference statements)
2
33
2
Order By: Relevance
“…The animals (commercial fattening hybrids, n = 25; 12 males, 11 females, one castrated male, one without documented sex; age 0−230 days; weight 0.7−95 kg) were euthanized in a time frame comparable to other experiments (Ondrovics et al, 2013;Gabner et al, 2012;Worliczek et al, 2010). All of the animals were raised conventionally Nickel et al (1996) and Tonar et al (2015).…”
Section: Animals and Specimen Preparationmentioning
confidence: 99%
“…The animals (commercial fattening hybrids, n = 25; 12 males, 11 females, one castrated male, one without documented sex; age 0−230 days; weight 0.7−95 kg) were euthanized in a time frame comparable to other experiments (Ondrovics et al, 2013;Gabner et al, 2012;Worliczek et al, 2010). All of the animals were raised conventionally Nickel et al (1996) and Tonar et al (2015).…”
Section: Animals and Specimen Preparationmentioning
confidence: 99%
“…The animals (commercial fattening hybrids, n = 17; 9 males, 6 females, 1 castrated male, 1 without documented sex; age 5-210 days; weight 0.7-90 kg) were euthanized during other experiments (Ondrovics et al 2013;Gabner et al 2012;Worliczek et al 2010). All of the animals were conventionally treated and handled in compliance with the European Convention on Animal Care.…”
Section: Animals and Specimen Preparationmentioning
confidence: 99%
“…Phenotyping of cells after primary infection revealed that several subpopulations of T-cells (especially γδ-T cells and, T H cells) were decreased in peripheral organs (blood, spleen) but increased in the jejunum upon infection), and after challenge infection (5 months after primary infection) these cell populations also produced interferon-γ (which is crucial for the defence against apicomplexan parasites) and were able to proliferate upon antigen stimulation [8, 48, 49]. Thus, despite considerable individual reactions, it can be assumed that C. suis can induce specific primary and adaptive immune reactions in pigs including the induction of an immunological memory.…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%